PENYELESAIAN SENGKETA KREDIT MACET AKIBAT DEBITUR WANPRESTASI DALAM SITUASI PANDEMI COVID-19 PADA BPR KITA, KUTA-BADUNG - Irlanda, Astrina Putri; Adi Sudharma, Kadek Januarsa (Yustitia, 2022)
The business activities carried out by BPR KITA are collecting and distributing funds to residents in the form of credit loans. Given COVID-19 pandemic, which implementation of lending carried out by BPRs did not run smoothly, as a result it resulted in congestion on credit or defaults, this factor was the cause of the inability of citizens to fulfill certain obligations from transactions and engagements that they had carried out. , resulting in the threat of default such as late payment of credit installments and other payments that have been previously agreed with the bank. This thesis research is empirical legal research which places more emphasis on field research. The research method used is descriptive qualitative method, using primary data and secondary data. The data collection technique used in the preparation of this thesis is an interview technique with the main director of BPR KITA. The results of this thesis research can be concluded that the cause of bad loans is due to a pandemic that has an impact on their business, resulting in a default by the debtor, so the settlement of bad credit disputes at BPR KITA uses a non-litigation method (outside the court), which takes a non-litigation approach. to the debtor and find a way out so that the debtor can carry out his obligations again.